COVID-19 testing in English care homes and implications for staff and residents. (22nd January 2021) - Micocci, Massimo; Gordon, Adam L; Allen, A Joy; Hicks, Timothy; Kierkegaard, Patrick; McLister, Anna; Walne, Simon; Hayward, Gail; Buckle, Peter
Abstract: Introduction: Care home residents are at high risk of dying from coronavirus disease 2019 (COVID-19). Regular testing, producing rapid and reliable results is important in this population because infections spread quickly, and presentations are often atypical or asymptomatic. This study evaluated current testing pathways in care homes to explore the role of point-of-care tests (POCTs). Methods: A total of 10 staff from eight care homes, purposively sampled to reflect care organisational attributes that influence outbreak severity, underwent a semi-structured remote videoconference interview. Transcripts were analysed using process mapping tools and framework analysis focussing on perceptions about, gaps within and needs arising from current pathways. Results: Four main steps were identified in testing: infection prevention, preparatory steps, swabbing procedure and management of residents. Infection prevention was particularly challenging for mobile residents with cognitive impairment. Swabbing and preparatory steps were resource-intensive, requiring additional staff resource. Swabbing required flexibility and staff who were familiar to the resident. Frequent approaches to residents were needed to ensure they would participate at a suitable time. After-test management varied between sites. Several homes reported deviating from government guidance to take more cautious approaches, which they perceived to be more robust. Conclusion: Swab-based testing is organisationally complex and resource-intensive in care homes. It needs to be flexible to meet the needs of residents and provide care homes with rapid information to support care decisions. POCT could help address gaps but the complexity of the setting means that each technology must be evaluated in context before widespread adoption in care homes.